Comparison of the Implementation of Digital and Conventional Learning Methods on Student Retention at MA Tuhfatul Ulum - Hasanah, Uswatun; Yuliana, Dyan; Seituni, Siti (Journal of Educational Sciences, 2026)
This study compares the effectiveness of digital and conventional learning methods on students' retention at MA Tuhfatul Ulum. Traditional methods, particularly lectures, dominate the educational process but have limited effectiveness in engaging students actively. In contrast, digital learning methods, such as educational games, provide an innovative approach that enhances student engagement and retention. This research uses a quantitative comparative method with a sample of 47 students. Data were collected through observation, structured interviews, questionnaires, and documentation. The results, analyzed using One-Way ANOVA, indicate a significant difference in retention scores between the digital learning group (Mean = 81.09) and the conventional learning group (Mean = 56.52), with a significance value of 0.000. These findings demonstrate that digital methods, which encourage active participation and multisensory engagement, significantly improve long-term memory retention compared to traditional methods. Therefore, the study recommends the integration of digital learning tools to enhance the effectiveness of teaching and learning.